Calculation of speckle-image contrast: methodological support and software implementation - M. M. Mezhennaya; K. N. Runkevich; I. V. Kishkevich; T. V. Kalilec; S. K. Dzik; D. V. Likhachevsky; R. A. Lashchetko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Methodical and software has designed to implement the method of speckle visualization. The treatment options has experimentally grounded. They are the most optimal from the point of view of compliance with the space-time resolution and computation time.